2014
DOI: 10.1142/s0218957714500031
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and E Supplementation Versus Standard Meloxicam Regimen in the Treatment of Patients With Chronic Degenerative Arthritis of the Knee: A Preliminary Pilot Study

Abstract: Objectives: To investigate the effectiveness of vitamin C and E supplementation in remission of the symptoms of chronic degenerative arthritis (osteoarthritis) of the knee. Design: A pilot controlled trial conducted from December 2009 until April 2011 among 46 patients diagnosed with osteoarthritis (OA) in one or both knees. Intervention: Patients were randomly assigned to two different treatment groups and were either supplemented with ascorbic acid 1 gr × 2 daily per os together with vitamin E 100 mg × 3 dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…After 20 days, both treatment groups demonstrated similar improvements in WOMAC and pain visual analog scale ( Oikonomidis et al, 2014 ). They also improved extension and flexion deficits in the patients, but the effect of meloxicam was limited to patients with severe-extreme osteoarthritis ( Oikonomidis et al, 2014 ). The total antioxidant capacity of the synovial fluid was significantly enhanced in the vitamin C + vitamin E supplemented group compared to meloxicam control ( Oikonomidis et al, 2014 ).…”
Section: The Relationship Between Vitamin E and Osteoarthritis In Hummentioning
confidence: 92%
See 3 more Smart Citations
“…After 20 days, both treatment groups demonstrated similar improvements in WOMAC and pain visual analog scale ( Oikonomidis et al, 2014 ). They also improved extension and flexion deficits in the patients, but the effect of meloxicam was limited to patients with severe-extreme osteoarthritis ( Oikonomidis et al, 2014 ). The total antioxidant capacity of the synovial fluid was significantly enhanced in the vitamin C + vitamin E supplemented group compared to meloxicam control ( Oikonomidis et al, 2014 ).…”
Section: The Relationship Between Vitamin E and Osteoarthritis In Hummentioning
confidence: 92%
“…The authors postulated that the reduction in nitrative stress shown by nitrotyrosine staining contributed to the analgesic effects of vitamin E shown in this study. The combination of vitamin C (1 g 2 times daily) and vitamin E (100 mg 3 times daily) had also been compared against meloxicam (15 mg oral daily) treatment in 46 osteoarthritic patients ( Oikonomidis et al, 2014 ). After 20 days, both treatment groups demonstrated similar improvements in WOMAC and pain visual analog scale ( Oikonomidis et al, 2014 ).…”
Section: The Relationship Between Vitamin E and Osteoarthritis In Hummentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed improvement in both clinical signs and inflammatory markers. [14][15][16][17][18][19][20][21] The only study investigating the use of VE in dogs was conducted after surgical transection of the cranial cruciate ligament and found that supplementation improved lameness and pain scores. 21 In addition, it decreased the severity of the cartilage damage observed on necropsy examination and resulted in decreased concentrations of nitric oxide and prostaglandins in the synovial fluid.…”
mentioning
confidence: 99%